THE TYPICAL PATHOCHEMICAL REACTIONS OF THE DAMAGING IMPACT OF DETERGENTS AS SOURCES OF RADIOTOXINS - T.M. Popova; N.V. Zharova; I.L. Kolesnik; A.V. Apolonina; V.V. Pogorelov; A.V. Titkova; I.Yu. Bagmut; V.I. Zhukov (Проблеми екології та медицини)
The mechanism of biological impact of detergents to the organisms of laboratory animals was researched. The detergents have properties of surface active agents and stimulate the reactions of free radical oxidation of lipids. This causes to the accumulation of peroxides, hydroperoxides and free radicals, diene conjugates, malonic dialdehyde. At the same time, propionic and acetic aldehyde, acetone, alcohols and other low-molecular-weight metabolites are formed by microsomal oxidation of the detergents. All these products are emitters of radiotoxins. The accumulation of peroxides, hydroperoxides and free radicals, malonic, acetic, propionic aldehydes, acetone, alcohol leads to depletion of the antioxidant system, i.e. the concentrations of SH - group, glutathione, vitamin C, haptoglobin, epinephrine, norepinephrine, microelements Fe2+, Cu2+, Mg2+ are reduced in the organs of the animals. The activity of catalase, peroxidase, glutathione peroxidase, lactate dehydrogenase, monoamine oxidase, ceruloplasmin, Ca2 +, Mg2 + -ATPase is decreased in organisms of experimental animals are treated by surface active agents for a long time. Activity of marker enzymes of cytoplasmic membranes – Na +, K + - ATPase, adenylate cyclase is decreased by disturbance of membrane structure, quantitative and qualitative changes of characteristics of the phospholipid layer. Radiomimetic action of the detergents such as stimulation of free radical pathology in the organism is a conceptual model of the mechanism of their biological action.